2020
DOI: 10.1016/j.thromres.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of indirect markers of hypercoagulability with thromboelastography in severe coronavirus 2019

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Reduced fibrinolytic activity was also observed in patients with COVID-19, with all studies reporting LY30 less than 1%, including three which showed complete fibrinolytic shutdown (LY30 of 0%) [ 18 , 23 , 25 ]. A shortened R-time of less than 5 min was observed in patients from four studies [ 18 , 20 , 22 , 26 ], indicating a shorter time to clot formation in hypercoagulable patients, although the R-value was within the range of normal in most studies ( Figure 4 ), implying that the change in R-time is less consistent than the increased MA [ 5 , 14 , 15 , 19 ] and fibrinolytic shutdown in the characterization of COVID-19. Platelet function, measured by the PlateletMapping ADP assay, was in the high normal range for the majority (81%) of patients with COVID-19 in the one study where this parameter was measured [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced fibrinolytic activity was also observed in patients with COVID-19, with all studies reporting LY30 less than 1%, including three which showed complete fibrinolytic shutdown (LY30 of 0%) [ 18 , 23 , 25 ]. A shortened R-time of less than 5 min was observed in patients from four studies [ 18 , 20 , 22 , 26 ], indicating a shorter time to clot formation in hypercoagulable patients, although the R-value was within the range of normal in most studies ( Figure 4 ), implying that the change in R-time is less consistent than the increased MA [ 5 , 14 , 15 , 19 ] and fibrinolytic shutdown in the characterization of COVID-19. Platelet function, measured by the PlateletMapping ADP assay, was in the high normal range for the majority (81%) of patients with COVID-19 in the one study where this parameter was measured [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were also data showing thromboelastography could better identify and assess hypercoagulability in patients with COVID-19 than laboratory coagulation tests such as PT and aPTT, which were found to be either normal or slightly prolonged with medians (range) 1.16 (0.99–1.50) and 0.98 (0.78–1.24), respectively [ 7 ]. In a study by Hightower et al, thromboelastography was able to identify coagulopathic states where laboratory coagulation tests could not [ 18 ]. In the study by Lawicki et al, the observation of elevated CFF-MA in all patients with COVID-19, and results within normal reference ranges for all patients without disease, was in contrast to observations for laboratory measures such as D-dimer, C-reactive protein, ferritin and procalcitonin, which were not consistently elevated in patients with COVID-19, and of which elevations were also common in patients without COVID-19 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hightower et al observed the TEG profile of a small cohort of patients with COVID-19 and found that dysregulation of the fibrinolytic system is responsible for the hypercoagulable state. 14 Maatman et al analyzed TEG data of 12 patients admitted to ICU with severe COVID and found that 58% of them had a hypercoagulable state. 15 Panigada et al studied 24 patients and found a state of hypercoagulability as shown by decreased R and K values, and increased values of ANGLE and MA.…”
Section: Discussionmentioning
confidence: 99%
“…VETs were performed using ROTEM (25 studies), TEG (15 studies), Quantra (two prospective studies [66,67]) and ClotPro (one retrospective study [24] and one case report [68]); no study compared two devices. Among articles reporting data about TEG, four were prospective studies [52,[59][60][61], ten were retrospective studies [51,[53][54][55][56][57][58][62][63][64], and one was a case report [65]. Among articles dealing with ROTEM, thirteen were prospective studies [28][29][30][31][32][39][40][41][42][43][44][45][46], seven were retrospective studies [27,[33][34][35][36]48,49], one was a cross-sectional study [47], and four were case reports [26,37,38,50].…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%